Estudio económico para la implementación de una red de fibra óptica en el cantón Daule para potenciar el crecimiento socioeconómico del sector - Camacho Aguayo, Diego Armando (2019)
The present economic study proposes the implementation of a fiber optic network in the parishes Laurel, Juan Bautista Aguirre and El Limonal of the city of Daule, which specifically contributes to the quality of life of the inhabitants in this rural area, not only at the level of communication and information, but also at the socioeconomic level, since having this type of infrastructure, internet and all its integrated services can be more efficient. At present, the internet service is considered a basic service and, if so, users have stable and high-speed browsing. A fiber optic network, the quality is foreign to problems caused by external agents, would allow connections to the Internet with greater stability and therefore greater speed……..